2021
DOI: 10.3390/cancers13112532
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Care in Patients with Head and Neck Cancer during Chemoradiotherapy (CRT) and Bioradiotherapy (BRT) Provides Better Compliance with the Treatment Plan

Abstract: The treatment of locally advanced head and neck cancer (HNC) is based on extensive resections followed by concurrent chemoradiotherapy (CRT) with platinum derivatives or concurrent radiotherapy with cetuximab (bioradiotherapy; BRT). Malnutrition, which occurs in up to 60% of patients before treatment commencement, severely increases the risk of CRT/BRT drug dose reductions and the incidence of treatment-related adverse events. A prospective observational study was performed regarding the influence of nutrition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 42 publications
0
8
0
1
Order By: Relevance
“…A recent study from our unit has shown that an organized care program provided by the specialized nutrition team results in reduced rates of Aes, prevents down-dosing of oncological treatment and reduces weight loss in patients with HNC. 19 Another key finding in our study was that PEGs performed in patients following oncological treatment (CRT) had an almost 3-fold higher risk of major Aes than patients before such treatment (HR = 2.7, 95% CI = 1.0-7.2, p = 0.042). This finding supports the beneficial role of early ("prophylactic") PEG rather than "reactive" PEG placement.…”
Section: Procedural Datamentioning
confidence: 58%
See 1 more Smart Citation
“…A recent study from our unit has shown that an organized care program provided by the specialized nutrition team results in reduced rates of Aes, prevents down-dosing of oncological treatment and reduces weight loss in patients with HNC. 19 Another key finding in our study was that PEGs performed in patients following oncological treatment (CRT) had an almost 3-fold higher risk of major Aes than patients before such treatment (HR = 2.7, 95% CI = 1.0-7.2, p = 0.042). This finding supports the beneficial role of early ("prophylactic") PEG rather than "reactive" PEG placement.…”
Section: Procedural Datamentioning
confidence: 58%
“…With this in mind, it is of the utmost importance that these patients remain under the supervision of the Nutrition Clinic for regular monitoring of the PEG tube position within the first months after its placement. A recent study from our unit has shown that an organized care program provided by the specialized nutrition team results in reduced rates of Aes, prevents down‐dosing of oncological treatment and reduces weight loss in patients with HNC 19 …”
Section: Discussionmentioning
confidence: 99%
“…In our study, different stages of cachexia were significantly associated with treatment-related events. 26 The exact mechanism by which higher cachexia stages lead to an increase in the occurrence of treatment-related events is unknown, but certain factors may be involved. For example, radiation-induced fatigue is known to be associated with elevated levels of proinflammatory cytokines, including TNF-α and IL-6, both of which are elevated in cachexia patients.…”
Section: Discussionmentioning
confidence: 99%
“…Studies show that prophylactic PEG in patients with HNC undergoing chemoradiotherapy is associated with less weight loss and hospital readmission than in the reactive placement group ( 22 ). Kapała et al proved in the Polish study that an organized nutritional care program introduced and supervised by the specialized nutrition team (NST) reduced complication rates, prevented down-dosing of oncological treatment, and weight loss of patients with HNC ( 23 ). A growing number of patients with cancer on HEN are observed in European studies.…”
Section: Discussionmentioning
confidence: 99%